Emergence of Within-Host SARS-CoV-2 Recombinant Genome After Coinfection by Gamma and Delta Variants: A Case Report - Francisco Junior, Ronaldo da Silva; Almeida, Luiz G. P. de; Lamarca, Alessandra P.; Cavalcante, Liliane; Martins, Yasmmin; Gerber, Alexandra L.; Guimarães, Ana Paula de C.; Salviano, Ricardo Barbosa; dos Santos, Fernanda Leitão; de Oliveira, Thiago Henrique; de Souza, Isabelle Vasconcellos; de Carvalho, Erika Martins; et al. (Frontiers in Public Health, 2022)
In this study, we report the first case of intra-host SARS-CoV-2 recombination during a coinfection by the variants of concern (VOC) AY.33 (Delta) and P.1 (Gamma) supported by sequencing reads harboring a mosaic of lineage-defining mutations. By using next-generation sequencing reads intersecting regions that simultaneously overlap lineage-defining mutations from Gamma and Delta, we were able to identify a total of six recombinant regions across the SARS-CoV-2 genome within a sample. Four of them mapped in the spike gene and two in the nucleocapsid gene. We detected mosaic reads harboring a combination of lineage-defining mutations from each VOC. To our knowledge, this is the first report of intra-host RNA-RNA recombination between two lineages of SARS-CoV-2, which can represent a threat to public health management during the COVID-19 pandemic due to the possibility of the emergence of viruses with recombinant phenotypes.